Potential of Nanoparticles Integrated with Antibacterial Properties in Preventing Biofilm and Antibiotic Resistance - Maheswary Thambirajoo; Manira Maarof; Yogeswaran Lokanathan; Haliza Katas; Nur Fatiha Ghazalli; Yasuhiko Tabata; Mh Busra Fauzi (Antibiotics, 2021)
Nanotechnology has become an emerging technology in the medical field and is widely applicable for various clinical applications. The potential use of nanoparticles as antimicrobial agents is greatly explored and taken into consideration as alternative methods to overcome the challenges faced by healthcare workers and patients in preventing infections caused by pathogenic microorganisms. Among microorganisms, bacterial infections remain a major hurdle and are responsible for high morbidity and mortality globally, especially involving those with medical conditions and elderly populations. Over time, these groups are more vulnerable to developing resistance to antibiotics, as bacterial biofilms are difficult to destroy or eliminate via antibiotics; thus, treatment becomes unsuccessful or ineffective. Mostly, bacterial biofilms and other microbes can be found on medical devices and wounds where they disperse their contents which cause infections. To inhibit biofilm formations and overcome antibiotic resistance, antimicrobial-loaded nanoparticles alone or combined with other substances could enhance the bactericidal activity of nanomaterials. This includes killing the pathogens effectively without harming other cells or causing any adverse effects to living cells. This review summarises the mechanisms of actions employed by the different types of nanoparticles which counteract infectious agents in reducing biofilm formation and improve antibiotic therapy for clinical usage.